Living birth following preimplantation genetic testing for monogenic disorders to prevent low-level germline mosaicism related Nicolaides–Baraitser syndrome - Pan, Jiexue; Li, Jie; Chen, Songchang; Xu, Chenming; Huang, Hefeng; Jin, Li (Frontiers in genetics, 2022)
Objective: Paternal sperm mosaicism has few consequences for fathers for mutations being restricted to sperm. However, it could potentially underlie severe sporadic disease in their offspring. Here, we present a live birth of a female infant from a father with low-level sperm DNA mosaicism achieved via preimplantation genetic testing for monogenic disorders (PGT-M). Methods: A couple with the father carrying sperm DNA mosaicism received standard in vitro fertilization treatment, with intracytoplasmic sperm injection, embryo biopsy, polymerase chain reaction, and DNA analysis. Only one unaffected embryo was transferred to the uterine cavity. Amniocentesis was performed at the 16th week of gestation by copy-number variation-sequencing, karyotyping, and Sanger sequencing. Results: Eight surviving embryos were biopsied during the blastocyst stage. Karyomapping and Sanger sequencing were applied to detect the euploidy and paternal mutation. After performing PGT-M, followed by successful pregnancy, the prenatal genetic diagnoses revealed that the fetus was unaffected, and one healthy girl was born. Conclusion: This is the first reported live birth with unaffected children achieved via PGT for a low-level germline mosaicism father. It not only opens the possibility of preventing the recurrent monogenic disease of children among gonadal mosaicism families but also alerts clinicians to consider gonadal mosaicism as the source of DMNs.